Perceptions of disaster preparedness among older people in South Korea. (14th July 2015) - Yoo, Myoungran; Lee, Mijung; Tullmann, Dorothy
Abstract : Older people are a major vulnerable population. During disasters, given their physical frailty, lower social status, loss of medications and medical care, the vulnerability of older people increases. The purpose of this study was to examine the perceptions of older people in Korea on various aspects of disaster preparedness to better understand their special needs and to facilitate appropriate disaster planning. The study was qualitative and used focus group interviews with 12 older people in one major city and one rural area of South Korea. Four themes were identified by the analysis of the interviews: defenceless state, reality of accepting limitations, strong will to live, importance of disaster preparedness governmental efforts for the older people. Findings indicated that preparation of shelters and transportation was critical to help older people survive in times of disasters and suggested that there should be active involvement of the government in terms of disaster planning, managing and preparing older people for disasters. In addition, healthy older people can be assets to disaster relief efforts by providing practical and emotional support for the most fragile older people. Older people can also provide knowledge of their special needs to the government to improve their disaster response policy.